A system to manage the allocation of MSc Dissertations at University of Minho - Cabral, José (2010)
This paper describes the basis for the specification of an IT infrastructure, supported by a website, designed to manage the entire paperwork process associated with the management of Masters Dissertations. With this infrastructure it is possible to disclose the subjects offered, to allocate each subject to a candidate - "dissertations in progress", browse dissertations that are awaiting review and consult the archive of dissertations with exams already carried out. PostgreSQL technology was used to support the databases. This technology was chosen to be robust, with easy integration with PHP and its code is open source. The website is housed in a Linux server based infrastructure ready to run continuously.